Pharmacokinetic And Pharmacodynamic Assessment Of Etodolac Pharmacosomes In Experimental Models Of Rheumatoid Arthritis - Saxena, Sunanda; Goshain , Omprakash (Journal of Neonatal Surgery, 2025)
Background: Rheumatoid arthritis (RA) management using conventional NSAIDs is limited by systemic toxicity. Etodolac pharmacosomes offer targeted topical delivery with enhanced bioavailability and reduced adverse effects. Objective: To develop etodolac-phosphatidylcholine pharmacosomes and comprehensively evaluate their pharmacokinetic (PK) and pharmacodynamic (PD) profiles in established rodent models of RA. Methods: Pharmacosomes were prepared via solvent evaporation method and characterized for particle size (dynamic light scattering), zeta potential, entrapment efficiency, and morphology (transmission electron microscopy). Topical gel formulations were prepared using Carbopol 940. PK studies involved topical application to male Wistar rats (n=6) with plasma etodolac quantification by validated HPLC method. PD evaluation utilized carrageenan-induced paw edema (acute model) and Complete Freund's Adjuvant (CFA)-induced arthritis (chronic model). Anti-inflammatory efficacy was assessed via paw volume measurements, arthritic scoring, histopathological examination, and inflammatory biomarker quantification (TNF-α, IL-1β) by ELISA. Results: Optimized pharmacosomes exhibited mean particle size of 180±12 nm, zeta potential of -32±3 mV, and entrapment efficiency of 88±2%. In vitro drug release followed Higuchi kinetics with 75% release over 24 hours. Topical pharmacosome gel demonstrated superior PK profile: Cmax=4.2±0.4 μg/mL (vs. 1.6±0.2 μg/mL for plain gel), Tmax=6 hours, t½=15.4±2.1 hours, and 3.8-fold bioavailability enhancement (p<0.001). In carrageenan model, pharmacosome gel inhibited paw edema by 68±5% versus 35±4% for plain gel (p<0.001). In CFA-induced arthritis, treatment reduced arthritic scores by 72±6% (p<0.001) with preserved joint architecture on histopathology. Serum TNF-α and IL-1β levels were reduced by 65±7% and 59±6%, respectively (p<0.001). No skin irritation was observed in safety studies. Conclusion: Etodolac pharmacosomes demonstrate significantly enhanced topical delivery, superior PK/PD profiles, and potent anti-arthritic efficacy in experimental RA models. These findings support clinical development for RA management with potential for improved therapeutic outcomes and reduced systemic toxicity